IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR PASSING PERMAINAN BOLA BASKET PESERTA DIDIK KELAS XI SMK NEGERI 3 SEMARANG - Rahardian Damarjati; Dani Slamet Pratama (STKIP Subang, 2025)
This study aims to implement the Teaching at the Right Level (TaRL) approach to improve learning outcomes in basic passing techniques in basketball for grade XI students at SMK Negeri 3 Semarang. The method used is classroom action research (CAR) involving 35 students as subjects. The research was conducted in two cycles comprising planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and documentation, encompassing both qualitative and quantitative data. The results showed an improvement in learning outcomes across each cycle. The percentage of students achieving mastery increased from 37.1% in the pre-cycle stage to 60% in the first cycle and 80% in the second cycle. The average student score also increased from 73.6 to 80. The TaRL approach proved effective by grouping students based on their abilities and needs, thus creating more focused and participative learning experiences.